A study of the quality of life in patients with diverticular colon disease, after suffering attacks of diverticulitis - A. L. Levchuk; A. E. Abdullaev (Вестник хирургии имени И.И. Грекова)
The objective of the study was to evaluate the quality of life of patients with DCD after several episodes of exacerbations of the disease.Methods abd materials. A study was conducted with the participation of 110 patients treated at the State Clinical Hospital in Vladimir from 2019–2024 with DCD. There were 48 men (43.6 %) and 62 women (56.3 %). All patients were divided into 3 groups. Group 1 (n=38) (34.5 %) consisted of patients with one exacerbation during a year. Group 2 (n=24) (21.8 %) consisted of patients with two exacerbations during a Group 3 (n=48) (43.6 %) consisted of patients who had three exacerbations of DCD during a year. The results were evaluated within a period of at least a year from the last episode of the AD attack. The MOS-SF 36 questionnaire, the GIQLI – Gastrointestinal Quality of Life Index and the EQ-5D questionnaire were used to assess QOL.Results. In patients of group 1 (n=38) (34.5 %), we recorded the best clinical results after the treatment. According to the results of the QOL study using the SF-36 questionnaire: PF-28, RP-8, BP-2, GH-21, VT-15, SF-9, RE-6, MH-21. When analyzing the results on the GIQLI, a GI of 128± was recorded. When analyzing the results of the EQ-5D questionnaire, the best results were obtained. According to the visual analog scale (YOUR), health status level was 92± 3.5. In patients of group 2 (n=24) (21.8 %), we recorded changes in clinical results after treatment. According to the results of the QOL study using the SF-36 questionnaire, the following results were recorded: PF-19, RP-4, BP-7, GH-16, VT-12, SF-6, RE-3, MH-17. When analyzing the results on the GIQLI, the GI was 98±4. When analyzing the results of the EQ-5D questionnaire, 18 (16.3 %) patients experienced some difficulty walking. According to the visual analog scale, the level of health status was 84 ± 3.5. The patients of group 3 (n=48) (43.6 %) had the worst clinical results. According to the results of the study, using the SF-36 questionnaire, the following results were recorded: PF-15, RP-5, BP-7, GH-16, VT-16, SF-7, RE-3, MH-19. When analyzing the results on the GIQLI, the GI was 82±4. When analyzing the results of the EQ-5D questionnaire, the worst results were recorded. According to the visual analog scale, the level of health status was 75±1.2.Conclusion. The decision on the surgical treatment of patients with DCD must be justified in each case individually, taking into account the study of the quality of life, the clinical picture of the progressive development of the disease and the assessment of the risk of possible severe complications.